(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
A field experiment was conducted to evaluate the effects of pre-sowing treatment of calcium chloride and phosphorus fertilization individually and combinely on the yield, oil content and physico-chemical properties of groundnut. This experiment consists of three pre-sowing treatments of calcium chloride solution (0%, 0.15%, 0.25%,0.50%) and four doses of phosphorus (0,30,45,60,75 kg/ha) with control. Pod yield of groundnut found 2.25 t/ha was maximum at 0.50% calcium chloride presowing treatment. The number of pods/plant (26.86) as well as, weight of 100 seeds (88.49) found significantly increased by applying 75 kg P2O5 / hectare when compared to the control. From the interaction of pre-sowing and fertilizer treatments, ie, 0.50% pre-sowing of calcium chloride (T3 ) with 75 kg P2O5 / hectare ( P4) produced significantly increased of pod yield (2.54 t / ha) and oil content (47.25%) of groundnut. Responses of pre-sowing and fertilization treatments on physico-chemical properties of groundnut oil such as refractive index, peroxide value, density remained unchanged throughout this experiment. Key words: Groundnut, Presowing, Calcium chlorid, Phosphorus, Oil content. DOI: 10.3329.bjsir.v43i1.854 Bangladesh J. Sci. Ind. Res. 43(1), 29-36, 2008